Genetic Analysis Of Fitness Traits Of Corriedale Sheep Under Temperate Conditions Of Kashmir (Applied Biological Research, 2020)
Pedigree information data for 49 years (1969-2017) for fitness traits  maintained at Mountain Research Centre for Sheep and Goat (MRCSG),  SKUAST-K Shuhama Kashmir was analyzed to evaluate the performance  of Corriedale sheep under the temperate agro-climatic conditions of  Jammu & Kashmir state. The effects of non-genetic factors such as period  of birth and sex on various normalized fitness traits such as age at first  lambing (AFL), litter size (LS), total lambs born perewe (TLB) and  survival rate (SR) were analyzed by least squares analysis. The period of  birth was found to have highly significant (p < 0.01) effect on all the traits  studied. The least square means revealed that lambs born in period 1969- 1975 had higher values of TLB, higher percentage of SR and lowest value  of ALF. Sex of lamb had significant (p < 0.05) effect on SR. The heritability  estimates were 0.09 ± 0.01, 0.40 ± 0.04, 0.29 ± 0.07 and 0.23 ± 0.03 for AFL,  LS, TLB and SR, respectively. The study revealed that AFL and fitness traits are influenced by both genetic and non-genetic factors. Therefore,  improvement in these traits in the flock can be achieved through selection  and management.
Keywords: Age at first lambing; Corriedale sheep; litter size; heritability; survival rate